2007
DOI: 10.5194/angeo-25-1815-2007
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis on spatial correlation of ionospheric day-to-day variability by using GPS and Incoherent Scatter Radar observations

Abstract: Abstract. In this paper, the spatial correlations of ionospheric day-to-day variability are investigated by statistical analysis on GPS and Incoherent Scatter Radar observations. The meridional correlations show significant (>0.8) correlations in the latitudinal blocks of about 6 degrees size on average. Relative larger correlations of TEC's day-to-day variabilities can be found between magnetic conjugate points, which may be due to the geomagnetic conjugacy of several factors for the ionospheric day-to-day va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 33 publications
3
62
1
Order By: Relevance
“…Thus, its principal behavior agrees with the TEC correlation analyses of Shim et al (2008). Furthermore, we observe the temporal evolution of the horizontal covariance reaching its peak at 12:00 on day of year (DOY) 22 (2011) coinciding with the local time variations of the TEC correlation distances described in Yue et al (2007).…”
Section: Relationship Between Electron Density Covariance and Stec Mesupporting
confidence: 71%
See 2 more Smart Citations
“…Thus, its principal behavior agrees with the TEC correlation analyses of Shim et al (2008). Furthermore, we observe the temporal evolution of the horizontal covariance reaching its peak at 12:00 on day of year (DOY) 22 (2011) coinciding with the local time variations of the TEC correlation distances described in Yue et al (2007).…”
Section: Relationship Between Electron Density Covariance and Stec Mesupporting
confidence: 71%
“…Bust et al (2004) suggested the separation of the spatial covariance model into horizontal and vertical components to take the geometric anisotropy of the ionosphere, i.e., directionally dependent correlation lengths, into account. Yue et al (2007) and Shim et al (2008) confirmed this approach with the analysis of GPS and incoherent scatter radar observations revealing different correlation lengths in latitude, longitude and height direction. Furthermore, the investigations of Blanch et al (2003) and Pèrez (2005) show that the exponential covariance model might be appropriate to describe spatial dependencies of the ionosphere.…”
Section: Spatial Covariance Model Of Electron Densitysupporting
confidence: 59%
See 1 more Smart Citation
“…However, our approach is based on the research of the ionospheric spatial correlation (e.g. Klobuchar and Kunches 2000;Yue et al 2007). It is well-known that the correlation distance of the ionosphere depends on direction and can be regarded as anisotropic.…”
Section: Comparative Analysismentioning
confidence: 99%
“…We developed a global ionospheric data assimilation model based on some previous studies [32], [33], [35], [37]. The key parameters of the model, including spatial and temporal resolutions, background and observation covariances, and background models, can be customized by the user.…”
Section: Global Ionospheric Data Assimilation Modelmentioning
confidence: 99%